2019
DOI: 10.3389/frobt.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

Introducing ACASS: An Annotated Character Animation Stimulus Set for Controlled (e)Motion Perception Studies

Abstract: category) within the database. The ACASS database and its subsets provide unique opportunities for research applications in social psychology, social neuroscience, and applied clinical studies on communication disorders. All 792 AVI-files, selected subsets, MATLAB code, annotations, and motion capture data (FBX-files) are available online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In games, for instance, many sub-scenes are prerecorded and thus the same for all audience members, and the same holds true for VR. Moreover, for both games and VR experiences, it is exceptionally well possible to quantify and precisely time-lock contents ( Bente et al, 2007 ; Huskey et al, 2018a ; Lammers et al, 2019 ; Calcagnotto et al, 2021 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…In games, for instance, many sub-scenes are prerecorded and thus the same for all audience members, and the same holds true for VR. Moreover, for both games and VR experiences, it is exceptionally well possible to quantify and precisely time-lock contents ( Bente et al, 2007 ; Huskey et al, 2018a ; Lammers et al, 2019 ; Calcagnotto et al, 2021 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…To avoid ceiling effects in emotion recognition due to the use of explicit expressive gestures, e.g., a fist clinch (see for instance Aviezer et al, 2012;Reynolds et al, 2019), we used stimulus material from recently published animation database ACASS (Lammers et al, 2019). The database consists of motion capture recordings of actors performing manual tasks (such as painting, mopping, sanding) in different moods (angry, happy, sad).…”
Section: The Current Studymentioning
confidence: 99%
“…Animation stimuli were taken from a recently published database ACASS (Annotated Character Animation Stimulus Set; Lammers et al, 2019). ACASS consists of motion capture datasets of human actors performing six different everyday activities (sweeping, wiping a table, painting with a roller, painting with a brush, mopping, sanding a table) in three different moods (angry, happy, sad).…”
Section: Stimulus Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found participants with ASD to have difficulties in MENT-but not in MNS-related parts of a novel paradigm (Marx, 2018). The paradigm used by Marx was developed to specifically activate MNS and MENT with as little differences between conditions as possible (Lammers, 2017;Lammers et al, 2019). It utilizes motion capture based animations of two everyday activities (mopping, sweeping), each carried out in two moods (angry, happy).…”
Section: Movement Perception and Production In Asdmentioning
confidence: 99%